2023
DOI: 10.3390/microorganisms11061572
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sea Ice Cover on Microbial Communities in Antarctic Shelf Sediments

Abstract: The area around the Antarctic Peninsula (AP) is facing rapid climatic and environmental changes, with so far unknown impacts on the benthic microbial communities of the continental shelves. In this study, we investigated the impact of contrasting sea ice cover on microbial community compositions in surface sediments from five stations along the eastern shelf of the AP using 16S ribosomal RNA (rRNA) gene sequencing. Redox conditions in sediments with long ice-free periods are characterized by a prevailing ferru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…At the study site, this taxon likely plays an important role as indicated by its high relative abundance in the in situ sediments ( Supplementary Figure S8 ) and its high presence already at the start and throughout the experiment. This is in agreement with previous studies investigating Antarctic sediments ( Aromokeye et al, 2021 ; Baloza et al, 2023 ) and sub-Antarctic sediments around South Georgia ( Wunder et al, 2021 ). Sva1033 was shown before to oxidize acetate and reduce iron oxides in sediments of Potter Cove ( Aromokeye et al, 2021 ; Wunder et al, 2021 ), and also here it showed higher relative 16S rRNA abundance in acetate amended treatments.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…At the study site, this taxon likely plays an important role as indicated by its high relative abundance in the in situ sediments ( Supplementary Figure S8 ) and its high presence already at the start and throughout the experiment. This is in agreement with previous studies investigating Antarctic sediments ( Aromokeye et al, 2021 ; Baloza et al, 2023 ) and sub-Antarctic sediments around South Georgia ( Wunder et al, 2021 ). Sva1033 was shown before to oxidize acetate and reduce iron oxides in sediments of Potter Cove ( Aromokeye et al, 2021 ; Wunder et al, 2021 ), and also here it showed higher relative 16S rRNA abundance in acetate amended treatments.…”
Section: Discussionsupporting
confidence: 94%
“…It has been studied in different Arctic, manganese oxide rich sediments of the Barents Sea ( Vandieken et al, 2006c ), Beaufort Sea ( Magen et al, 2011 ) and Svalbard fjords ( Vandieken et al, 2006a ; Wehrmann et al, 2014 ). There are only few studies that investigated specific organic matter degradation processes, e.g., iron reduction, and the related microbial communities in Antarctic subsurface sediments ( Monien et al, 2014a ; Aromokeye et al, 2021 ; Wunder et al, 2021 ; Baloza et al, 2022 , 2023 ; Burdige and Christensen, 2022 ). The occurrence of manganese reduction and the respective microbial players have not been studied in any Antarctic sediments yet.…”
Section: Introductionmentioning
confidence: 99%